Use of purified F1845 fimbrial adhesin to study localization and expression of receptors for diffusely adhering Escherichia coli during enterocytic differentiation of human colon carcinoma cell lines HT-29 and Caco-2 in culture. - Kerneis, S (1991)
Whole diffusely adhering Escherichia coli (DAEC) C1845 cells bearing the F1845 adhesive factor bind diffusely to differentiated human colon carcinoma cell lines HT-29 and Caco-2. By using antibodies directed against the purified fimbrial adhesin F1845 factor, the expression of the DAEC F1845-specific brush border receptors in the polarized human intestinal HT-29 and Caco-2 epithelial cells was studied by indirect immunofluorescence. A low level of DAEC F1845 receptors in undifferentiated intestinal cells was detected; they were localized in a cluster of cells. DAEC F1845 receptors were expressed at a high level in differentiated HT-29 and Caco-2 cells. DAEC F1845 receptors were expressed at a strikingly high level in the apical domains of the cells and developed during enterocytic differentiation in culture, in parallel with the apical expression of the intestinal brush border hydrolase, sucrase-isomaltase.